Identifikasi Kandungan Formalin dan Total Garam pada Ikan Teri Asin di Sentra Pasar Ikan Bulak Kecamatan Bulak Surabaya - Maria Ilani Ninul; Arlin Besari Djauhari (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Fish as a food ingredient that contains high protein rots quickly compared to other food ingredients. Salted fish is called salted fish. The results of preliminary research testing the formalin content of salted anchovy fish at the Bulak Fish Market Center, Bulak District, Surabaya, showed that it was positive for formalin content and from the results of measuring the salt content of salted anchovy fish at the Bulak Fish Market Center, Bulak District, Surabaya, it was known that the salt content contained in anchovies Salted fish is declared safe because within normal limits, namely 20%, the lowest salt content is found in the 19th trade which has the highest total salt, namely from the 9th trader with a total salt content of 8.30 ppm and from the titration results it is known that 20 anchovy samples contain formalin content. The highest formalin content is from the 9th trader, namely 162 ppm and the lowest formaldehyde content is from the 4th trader, namely 9 ppm